Characteristics of Ang-(1–7)/Mas-Mediated Amelioration of Joint Inflammation and Cardiac Complications in Mice With Collagen-Induced Arthritis - Wang, Zhongjie; Huang, Wenhan; Ren, Feifeng; Luo, Lei; Zhou, Jun; Huang, Dongmei; Jiang, Mei; Du, Huaan; Fan, Jinqi; Tang, Lin (Frontiers in Immunology, 2021)
Objectives: Rheumatoid arthritis (RA) is a disabling disease with a high incidence that is regularly accompanied by cardiovascular complications. The aim of this study was to investigate the mechanisms underlying Ang-(1-7) and its Mas receptor agonist (AVE0991) on joint inflammation and cardiac complications in a collagen-induced arthritis (CIA) model.Methods: Collagen type Ⅱ was injected into DBA/1 mice to construct an arthritis model. CIA mice were treated with Ang-(1-7) [2.0 mg/kg intraperitoneally] and AVE0991 [3.0 mg/kg intraperitoneally]. Paw thickness and the arthritic index were evaluated. A pathologic examination of the ankle joints and heart were performed. The serum levels of inflammatory cytokines (TNF- α, IL-1 β, IL-6, and CRP) were determined by ELISA. The MAPKs and NF- κB signaling pathways in joint tissues, and the TGF-β/Smad pathway and levels of α-SMA and β -MHC protein expression in cardiac tissues were assessed by Western blot. The levels of TGF- β/Smad pathway, α-SMA, and β-MHC RNA in cardiac tissues were analyzed by real time-PCR. The levels of RANKL and MMP3 expression in ankle joints were detected by immunohistochemistry and real time-PCR. Results: Ang-(1-7) and AVE0991 reduced the levels of inflammatory cytokines in CIA mice. Ang-(1-7) and AVE0991 inhibited the MAPKs and NF-κB signaling pathways in ankle joint tissues, reduced RANKL and MMP3 expression, and ameliorated local joint inflammation and bone destruction. In addition, Ang-(1-7) and AVE0991 attenuated the TGF- β/Smad signaling pathway, reduced the levels of α-SMA and β-MHC expression, and diminished inflammatory cell infiltration into the myocardial interstitium and myocardial interstitial fibrosis in the hearts of CIA mice.Conclusions: 1) Ang-(1-7) reduced inflammatory levels in the serum of CIA mice; 2) Ang-(1-7) alleviated joint damage caused by inflammation through the attenuation of NF-κB and MAPKs pathways; 3) Ang-(1-7) ameliorated inflammation-induced cardiac fibrosis by impeding the TGF-β/Smad pathway; and 4) amelioration of joint inflammation and cardiac complications by Ang-(1-7) was mediated through the Mas receptor. This study provides theoretical evidence for exploring novel clinical therapeutic approaches for RA and its cardiac complications.